Efeito de fontes de luz na microdureza de resinas compostas - Ribeiro, Benícia Carolina Iaskieviscz; Boaventura, Juliana Campiloza [UNESP]; Gaião, Ubiracy [UNESP]; Saad, José Roberto Cury [UNESP]; Candido, Maria Salete Machado [UNESP] (My University, 2011)
This study assessed the surface microhardness of compound resins cured by different light sources. Methods Three micro hybrid (Vit-l-escence, Amelogen Plus, Opallis) and one nanoparticle (Filtek Z350, 3M ESPETM Dental Products, St. Paul, USA) compound resins were selected. The resins were polymerized by a halogen light unit (Ultralux, Dabi Atlante, Ribeirão Preto, Brasil) with two tips, one semi-guided made of glass and another of painted acrylic and a LED-based source (UltraLume 2, Ultradent®, South Jordan, USA). Specimens constructed from a circular aluminum matrix were photopolymerized for 40 second after they received the compound resin and stored dry for 24 hours. After this period, a Vickers surface microhardness assay was performed, measuring the top (hardness 1) and base (hardness 2) surfaces four times each. Variance analyses were complemented by Newman-Keuls method, with significance set at 5%. Results The Opallis (FGM, Santa Catarina, Brasil) resin subjected to UltraLume 2 (Ultradent®, South Jordan, USA) obtained the lowest mean hardness values for the top surface. The Vit-l-escence (Ultradent®, South Jordan, USA) compound cured by Led UltraLume 2 (Ultradent®, South Jordan, USA) and by Ultralux PCP (Dabi Atlante, Ribeirão Preto, Brasil) halogen light obtained the highest mean hardness, followed by the Filtek Z350 (3M ESPETM Dental Products, St. Paul, USA) resin subjected to UltraLume 2 (Ultradent® South Jordan, USA). The Opallis (FGM, Santa Catarina, Brasil) resin cured by LED UltraLume 2 (Ultradent®, South Jordan, USA) also obtained the lowest mean hardness for the base surface and the Vit-L-Escence (Ultradent®, South Jordan, USA) resin obtained the highest value, followed by Amelogen Plus, when cured by Ultralux (Dabi Atlante, Ribeirão Preto, Brasil) using the semi-guided tip. Conclusion The polymerization and, consequently, the microhardness achieved by the LED unit was equivalent to those achieved by conventional halogen units for three of the four composites tested.

Avaliar a microdureza superficial de resinas compostas polimerizadas por diferentes fontes de luz. Métodos Foram selecionadas três resinas compostas microhíbridas (Vit-l-escence, Amelogen Plus, Opallis) e uma nanoparticulada (Filtek Z350, 3M ESPETM Dental Products, St. Paul, USA). Foram submetidas à polimerização utilizando-se um aparelho halógeno (Ultralux, Dabi Atlante, Ribeirão Preto, Brasil) com duas ponteiras, uma de vidro semi-orientada e outra de acrílico pintada e também um dispositivo à base de LED (UltraLume 2, Ultradent®, South Jordan, USA). Os corpos-de-prova obtidos a partir de uma matriz circular de alumínio, após receberem a resina composta, foram fotopolimerizados por 40 segundos e em seguida armazenados a seco por 24 horas. Decorrido esse período, procedeu-se ao ensaio de microdureza superficial Vickers, realizando-se quatro aferições na superfície de topo (dureza 1) e na superfície de base (dureza 2). Utilizou-se a análise de variância que foi complementada pelo teste de Newman-Keuls de comparações múltiplas de médias, ao nível de significância de 5%. Resultados No topo, as menores médias de dureza foram obtidas com a resina Opallis submetida ao UltraLume 2 (Ultradent®, South Jordan, USA). As médias maiores referem-se ao compósito Vit-l-escence (Ultradent®, South Jordan, USA) polimerizado com o Led UltraLume 2 (Ultradent®, South Jordan, USA) e luz halógena Ultralux PCP (Dabi Atlante, Ribeirão Preto, Brasil), seguidas da resina Filtek Z350 (3M ESPETM Dental Products, St. Paul, USA) submetida ao UltraLume 2 (Ultradent®, South Jordan, USA). Quanto à base, a menor média de dureza também foi da resina composta Opallis (FGM, Santa Catarina, Brasil), sob ação do LED UltraLume 2 (Ultradent®, South Jordan, USA) e a maior da Vit-l-escence (Ultradent®, South Jordan, USA), seguida pela Amelogen Plus (Ultradent®, South Jordan, USA) quando polimerizada pelo Ultralux (Dabi Atlante, Ribeirão Preto, Brasil) com a ponta semi-orientada. Conclusão O aparelho LED permitiu polimerização e consequentes valores de microdureza equivalentes ao dos aparelhos halógenos convencionais, para três dos quatro compósitos avaliados.
Effect of light sources on the microhardness of composite resins
Keywords: Hardness; Composite resins; Light; Dureza; Resinas compostas; Luz